Management of Islamic Religious Education (PAI) To Form Social Piety In Private Universities - Abidin, Zaenal (Interdiciplinary Journal and Hummanity (INJURITY), 2022)
Islamic Religious Education (PAI) in tertiary institutions is seen as a basis for building social foundations, academic and professional foundations. The implementation of Islamic Religious Education in tertiary institutions has a very urgent position for several rational reasons as follows: first, the influence of foreign culture, the impact of the digitalization era, frequent access to the internet students are trapped in things that are not good, such as pornography, online games, free lifestyle, very individualistic and less concerned with others. Second, general subjects (general science) are seen as more promising, because of the ease in finding a job. They see that the end of lectures is getting a decent job as expected. Third, the learning orientation is only towards material things, production and consumption. This study uses a theoretical basis that integrates management theory, Islamic religious education theory and social piety theory. Al-Qur'an and Al-Hadith as theological basis. While the philosophy of idealism as a philosophical basis. This research uses descriptive analytic method with a qualitative approach. Data collection techniques were carried out using the triangulation method through three approaches, namely in-depth interviews, observation and documentation. The purpose of this study is to describe and analyze the process of planning, organizing, implementing, and evaluating the management of Islamic religious education to form social piety at the Faculty of Islamic Religion, Universitas Islam Nusantara, Faculty of Tarbiyah and Teacher Training, Islamic University of Bandung. The results of this study draw the following conclusions: first, planning for Islamic Religious Education to form social piety; second, making arrangements for determining administrative and financial tasks; third, implementing the implementation of learning with two approaches, namely the theoretical approach and the practical approach; fourth:, evaluating the management process of Islamic Religious Education regarding the principles and objectives of Islamic Religious Education to form social piety effectively and efficiently. The learning model in this study went through several stages, starting from the selection of student admissions (input), the long and integrated process of Islamic learning (process). In order to produce students who have adequate academic, spiritual, and emotional-based social piety (output), so that they can become citizens who have social piety (outcome).